Structural Optimization of Non-Nucleotide Loop Replacements for Duplex and Triplex DNAs - Rumney, Squire (1995)
Described are studies systematically exploring structural effects in he use of ethylene glycol (EG) oligomers as non-nucleotide replacements for nucleotide loops in duplex and triplex DNAs. The new structurally optimized loop replacements are more stabilizing in duplexes and triplexes than previously described EG-based linkers. A series of compounds ranging in length from tris(ethylene glycol) to octakis(ethylene glycol) are derivatized as monodimethoxytrityl ethers on one end and phosphoramidites on the other, to enable their incorporation into DNA strands by automated methods. These linker molecules span lengths ranging from 13 to 31 Å in extended conformation. They are incorporated into a series of duplex-forming and triplex-forming sequences, and the stabilities of the corresponding helixes are measured by thermal denaturation. In the duplex series, results show that the optimum linker is the one derived from heptakis(ethylene glycol), which is longer than most previous loop replacements studied. This affords a helix with greater thermal stability than one with a natural T(4) loop. In the triplex series, the loop replacements were examined in four separate situations, in which the loop lies in the 5′ or 3′ orientation and the central purine target strand is short or extends beyond the loop. Results show that in all cases the loop derived from octakis(ethylene glycol) (EG(8)) gives the greatest stability. In the cases where the target strand is short, the EG(8)-linked probe strands bind with affinities in some cases greater than those with a natural pentanucleotide (T(5)) loop. For the cases where the target strand extends beyond the linker, the EG(8)-linked strands are much lower in the 5′ loop orientation than in the 3′ loop orientation. It is found that extension by one additional nucleotide in one of the bonding domains in the EG-linked series can result in considerably greater stabilities with long target strands. Overall, the data show that optimum loop replacements are longer than would be expected from simple distance analysis. The results are discussed in relation to expected lengths and geometries for double and triple helixes. The findings will be usefull in the design of synthetically modified nucleic acids for use as diagnostic probes, as biochemical tools, and as potential therapeutic agents.